PENGARUH PENGEMBANGAN SUMBER DAYA MANUSIA, DISIPLIN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS MUHADI SETIABUDI - Hendri Sucipto; Mukson; Muhammad Syaifulloh (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
The aims of this study are: 1) to determine and analyze the influence of humanresource development, work discipline, and work environment on employeeperformance at the Faculty of Economics and Business, Muhadi SetiabudiUniversity. 2) to determine and analyze the effect of human resource developmenton employee performance at the Faculty of Economics and Business, MuhadiSetiabudi University. 3) to determine and analyze the effect of work discipline onemployee performance at the Faculty of Economics and Business, MuhadiSetiabudi University. 4) to determine and analyze the effect of the workenvironment on the performance of employees at the Faculty of Economics andBusiness, Muhadi Setiabudi University. 5) to determine and analyze the influenceof human resource development, work discipline, and work environment onemployee performance at the Faculty of Economics and Business, MuhadiSetiabudi University. This type of research is survey and causal and involves 42subjects selected through the census method. Based on multiple linear regressiontest shows that: 1) the development of human resources, work discipline, and workenvironment simultaneously have a positive and significant effect on theperformance of the Faculty of Economics and Business, Muhadi SetiabudiUniversity. 2) human resource development has a positive and significant impacton the performance of the Faculty of Economics and Business, Muhadi SetiabudiUniversity. 3) work discipline has a positive and significant effect on theperformance of the Faculty of Economics and Business, Muhadi SetiabudiUniversity. 4) the work environment has a positive and significant effect on theperformance of the Faculty of Economics and Business, Muhadi SetiabudiUniversity. 5) There are differences in human resource development betweenStructural and Non-Structural Employees at the Faculty of Economics andBusiness, Muhadi Setiabudi University. There is no difference between workdiscipline and the work environment of Structural and Non-Structural Employeesat the Faculty of Economics and Business, Muhadi Setiabudi University